Assessing Gender Inequality among Italian Regions: The Italian Gender Gap Index - Monica Bozzano (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
This paper aims at exploring and evaluating the geographic distribution of gender inequality across Italian regions. The aim of the analysis is two-fold. First we build a composite indicator of gender inequality at the regional level for Italy by applying the methodology developed by the World Economic Forum for the Global Gender Gap Index. Second, we compute the Italian Gender Gap Index for each region in order to measure the within-country heterogeneity that characterizes Italy. We complete the analysis by presenting the correlation between the Italian Gender Gap Index and relevant socio-economic variables.
Keywords: 330; Italian Gender Gap Index; Italian regions; socio-economic gender inequality